2010
DOI: 10.1159/000317244
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Sleep Impairment in Persistent Allergic Rhinitis Patients Using Polysomnography

Abstract: Background: Although questionnaires have demonstrated an association between impairment of quality of sleep and symptoms in allergic rhinitis (AR) patients, to date there is no report of an objective assessment of sleep in patients with persistent allergic rhinitis (PER) as defined by ARIA guidelines. The aim of the present study was therefore to assess sleep disturbance in PER patients by polysomnography (PSG). Methods: Ninety-eight PER patients with moderate-to-severe nasal obstruction and 30 healthy volunte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 53 publications
(33 reference statements)
1
7
0
Order By: Relevance
“…46 Recently, a study investigating sleep impairment using PSG in patients with persistent AR showed that there were statistically significant, though clinically modest, differences between patients with persistent AR and healthy controls in most PSG parameters, including sleep efficiency, arousal index, average SaO 2 , lowest SaO 2 , time spent with a saturation below 90%, and snoring time. 47 However, AHI was similar for the two groups. Interestingly, the current study has demonstrated that compared to patients with OSA and without rhinitis, patients with NAR, rather than with AR, had significantly lower average SaO 2 saturation (91.9 ± 0.6 versus 94.0 ± 0.6) and minimal SaO 2 saturation (70.6 ± 1.7 versus 77.3 ± 1.8).…”
Section: Discussionmentioning
confidence: 82%
“…46 Recently, a study investigating sleep impairment using PSG in patients with persistent AR showed that there were statistically significant, though clinically modest, differences between patients with persistent AR and healthy controls in most PSG parameters, including sleep efficiency, arousal index, average SaO 2 , lowest SaO 2 , time spent with a saturation below 90%, and snoring time. 47 However, AHI was similar for the two groups. Interestingly, the current study has demonstrated that compared to patients with OSA and without rhinitis, patients with NAR, rather than with AR, had significantly lower average SaO 2 saturation (91.9 ± 0.6 versus 94.0 ± 0.6) and minimal SaO 2 saturation (70.6 ± 1.7 versus 77.3 ± 1.8).…”
Section: Discussionmentioning
confidence: 82%
“…PSG is the gold standard for the objective evaluation of sleep disorders. 11 We did not observe any negative or positive effects of Ah on daily somnolence. There was a slight difference in REM percentage of the Ah group, but the difference was not found to be significant.…”
Section: Discussionmentioning
confidence: 52%
“…10 Daytime somnolence also causes a significant decrease in patients’ QOL. 11 It has been previously shown that AR is a risk factor for OSAS, especially in children. 12 AR symptoms per se may also cause cortical arousal and sleep fragmentation.…”
mentioning
confidence: 98%
“…[19][20][21][22] McNicholas et al [19] clearly demonstrated that an increase in nasal resistance was directly associated with an increased AHI rate in parallel to corresponding changes in O 2 desaturation. Meng et al [23] reported that subjects with AR presented moderately more severe data in PSG compared to healthy controls. Although they did not find a significant difference in AHI between groups, rates of the subjects with AHI >5 was significantly higher in AR subjects than healthy control groups by chisquare test.…”
Section: Discussionmentioning
confidence: 99%